Cytoarchitectural changes in the developing cerebellar cortex of the laggard mutant mouse - Yunus, Junaedy; Setsu, Tomiyoshi; Kikkawa, Satoshi; Terashima, Toshio (Narra Sains Indonesia, 2025)
The laggard (lag) mutant mouse, which arises from a mutation in the Kif14 gene, begins to exhibit ataxia and impaired growth after the first postnatal week and subsequently dies prematurely around two weeks of age. In this mutant mouse, the layered architecture of the cerebellar cortex, cerebral cortex, dentate gyrus, and olfactory bulb is disrupted at the cellular level. The aim of this study was to identify the effect of Kif14 mutation on the development of the cerebellar cortex. Abnormalities in the cytoarchitectonics of the developing cerebellar cortex were assessed using hematoxylin-eosin (HE) staining and immunohistochemistry. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and bromodeoxyuridine (BrdU) assays were performed to identify apoptotic and proliferating cells. Macroscopic observation of the lag mutant cerebellum reveals a marked reduction in size compared to wild-type mice. HE staining displays a normal foliation and lamination pattern in the lag mutant cerebellum, but detailed analysis has shown morphological disorganization in the cytoarchitectonics of the cerebellar cortex. The mutant internal granular layer is poorly defined and contains significantly fewer granule cells. Meanwhile, Purkinje cells form multilayer arrangements instead of a monolayer arrangement, as observed in wild-type mice, with their dendritic arborization being severely underdeveloped. Some Purkinje cells exhibit multiple nuclei, suggesting that the Kif14 mutation disrupts normal cell division. These phenotypes are already recognized during early postnatal days, although no difference is determined before birth. TUNEL-positive cells are significantly more numerous in the mutant external granular layer, indicating that increased apoptotic cell death contributes to the diminished granule cell population in the lag mutant mouse. In conclusion, the lag mutant cerebellar cortex shows distinct structural abnormalities, suggesting that the Kif14-encoded protein exerts multifaceted roles in the development of the brain laminated structures as well as in myelin formation.